EXPLOITATION CHARACTERISTICS OF ZOOBENTHOS SPECIES WITH ECONOMIC VALUE AT THE THUY TRIEU LAGOON, KHANH HOA PROVINCE - Ngai, Phan Duc; Tuan, Vo Si; Long, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2016)
The exploitation characteristics of zoobenthos species with economic value at the Thuy Trieu lagoon, Vietnam were determined by data synthesis of previous researches and four field trips carried out from 2011 - 2015. The results have pointed out 11 benthic species that have primary economic value, in which crustaceans have dominance in species (7 species) and yield (78 - 80% of the entire commercial yield of benthic animal), especially Portunus pelagicus possesses 64 - 72% of the entire commercial yield of crustacean. The majority of benthic animal resources are epifauna, inhabit subtidal zone, sandy mud bottom and seagrass. Thuy Trieu lagoon has had high exploitation pressure, with density of boats, number of fisheries and average exploitation time being great and concentrating mainly in the dry season (70% of average total time of fishery/year), specially some types of fishery are destructive, artisanal and damage bottom, seagrass ecosystems (70% of total time of year). The average catch of fishery has dominance in the dry season (81% of total yield of fishery/year). Species composition and yield of benthic animal have decreased seriously. These changes were primarily determined to be caused by the considerable average time of fishing activities, especially artisanal destructive fisheries (net cages, electric fishing). The results of this study will contribute the scientific basis to further studies on the trophic relationship, food web and data to planning, zoning and appropriate exploitation of fisheries resources.